Sistema informático de comunicación interdepartamental en el cuerpo de bomberos “Casimiro Farfán” del cantón Bolívar - Ballén Faubla, Christian Alexis (2016)
With the purpose of improve the information and communication security in the fire department Casimiro Farfán of the Bolivar canton, it was proposed to implement a computer system to manage electronic mail and instant messaging in order to have quicker access to the information of the institution, Providing greater security and reliability, as well as avoiding spam. To guarantee a good service was used the operating system Centos that provides reliability and stability, The Zimbra email service which together with its innovative messaging was chosen to be implemented for its security, administration features and ease of use; And the instant messaging manager Zextras. The implementation of the communication computer system was adapted to the requirements of the organization, which was divided into four phases: analysis, proposal design, implementation and testing. Once the tools and design were chosen, we proceeded with the implementation, integrating the server first and then performing the respective installation of the communication tools. Subsequently, the firewall rules were configured to avoid viruses and other possible computer attacks. The domain was registered with the name: mail.bomberoscalceta.gob.ec. Installed the server and put in production tests were made to verify that the services work correctly, doing zimbra tests and the sending of mails. The implementation of this service allowed to manage interdepartmental communication in a timely manner, optimizing resources.